1665 In paediatric trauma patients is prehospital bypass compared to secondary transfer associated with reduced hospital and intensive care unit length of stay? A retrospective observational study. Issue 12 (22nd November 2022) - Hibberd, Owen; Price, James; Laurent, Amy; Agrawal, Shruti; Barnard, Edward
Abstract : Aims, Objectives and Background: In the UK over half of severely injured children are conveyed to a trauma unit (TU). A proportion of these are subsequently transferred to a major trauma centre (MTC). Most regional networks permit TU bypass to an MTC. However, data on patient-centered outcomes between models are limited. The objective of this study was to compare hospital and intensive care unit (ICU) length of stay (LOS) between bypass and secondary transfer cohorts. Method and Design: All paediatric trauma patients (meeting Trauma Audit Research Network (TARN) inclusion criteria) admitted to the East of England MTC (2015–2020) were included. Bypass was defined as >45min transport time to MTC; secondary transfer was defined as transfer from a TU <24hr. TARN data were cross-referenced with electronic patient records to link pre-hospital data, complications, and timings. Data are reported as number (percentage), and median [inter-quartile range]. Proportions were compared with a Fisher's exact test, and medians with a Mann-Whitney U test; reported a p-values. Data were analysed in Prism 9 for macOS. Results & Conclusion: A total of 232 patients (n=58 bypass, n=174 secondary transfer) were included. The median age was 9.8 [4.5–13.7] years, n=156 (67.2%) were male, and the median injury severity score was 17.0 [10.0–25.0]; not significantly different between groups, table 1 . The median time to definitive care was five hours greater in the TU cohort, table 1 . There was a significantly longer hospital LOS and ICU LOS in the bypass group, both p<0.001. We observed no difference in mortality at time of discharge between groups, but the secondary transfer cohort were more likely to have a good neurological recovery, table 1 . In this regional study of paediatric trauma, we found no evidence that bypass to an MTC was associated with better patient outcomes compared to secondary transfer, despite significant time delays in reaching definitive care.